2016
DOI: 10.1186/s40064-016-1741-4
|View full text |Cite
|
Sign up to set email alerts
|

Daily microhabitat shifting of solitarious-phase Desert locust adults: implications for meaningful population monitoring

Abstract: The Desert locust Schistocerca gregaria is a major world pest that causes substantial agricultural and economic damage. Effective pest control relies on effective monitoring, which requires knowledge of locust microhabitat selection. Yet little is known about microhabitat selection of solitarious adult locusts in the field. We conducted field surveys to investigate fine-scale diel temporal and spatial distributions of solitarious adults in the Sahara Desert in Mauritania, a major breeding and recession area. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…However, we frequently observed that dense aggregations occurred at certain night-roosting plants even within a uniform plant distribution in the field, so plant distribution alone cannot explain the aggregation formation. In S. gregaria , night-roosting plant preference influence on their distribution: solitarious nymphs and adults and gregarious adults selectively roost on relatively large plants during a night [ 18 , 19 , 20 ]. It is reasonable to assume that night-roosting plant preference of gregarious nymphs may lead aggregation.…”
Section: Introductionmentioning
confidence: 99%
“…However, we frequently observed that dense aggregations occurred at certain night-roosting plants even within a uniform plant distribution in the field, so plant distribution alone cannot explain the aggregation formation. In S. gregaria , night-roosting plant preference influence on their distribution: solitarious nymphs and adults and gregarious adults selectively roost on relatively large plants during a night [ 18 , 19 , 20 ]. It is reasonable to assume that night-roosting plant preference of gregarious nymphs may lead aggregation.…”
Section: Introductionmentioning
confidence: 99%
“…For example, many warm‐blooded mammal insectivores such as jerboas ( Jaculus jaculus ) and hedgehogs avoid high daytime temperatures by hunting at night, when its cooler, but also when their high body temperatures allow them to easily overcome cold‐chilled invertebrates. Locusts avoid such nocturnal ground predators by roosting in large bushes and trees (Maeno & Ould Babah Ebbe, ; Maeno et al, , ). Although a few nocturnal mammals do hunt in trees, the size, complex branching and three‐dimensional architecture of trees, as well as the roosting height, make it difficult for such predators to find roosting locusts when the locusts are at low density (Maeno et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Locusts avoid such nocturnal ground predators by roosting in large bushes and trees (Maeno & Ould Babah Ebbe, ; Maeno et al, , ). Although a few nocturnal mammals do hunt in trees, the size, complex branching and three‐dimensional architecture of trees, as well as the roosting height, make it difficult for such predators to find roosting locusts when the locusts are at low density (Maeno et al, ). When locusts are at medium or high densities, aggregating together in tall trees at night produces another effective defence: predator‐swamping (= dilution effect).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In marked contrast, the solitarious locusts' life history involves very different and major 254 challenges in the path to successful mating and reproduction. These include: (1) locating 255 a mate: while both male and female solitarious locusts may participate in mate location, 256 it is accepted that it is mainly the males that are faced with the challenge of searching for 257 and locating the females in a scarce population (Ely et al, 2006;Maeno et al, 2016); 258…”
Section: Therein) 187mentioning
confidence: 99%